Thinking in cytology key - Francisco Javier Torres Gómez; Rosa Sánchez de Medina González; Beatriz Bravo Zambrano; Vanesa Ortega Bravo (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2022)
As pathologists, cytotechnologists, and professors of pathology and cytology, we find ourselves disconcerted because we turn, in disbelief, to an unprecedented situation that could affect patient care and we refer to the exact opposite of that which could be considered in any medical treatise or scientific article from the 20th century.